Research of Bias in Selected Journals: A Meta-Analysis - Necas, Vlastimil (Bodhi: An Interdisciplinary Journal, 2010)
This article deals with the possibilities of the approach to the study of the issue of bias in selected journals in the fields of Journalism and Media Studies. It mainly focuses on two areas: first, on work with the term "bias" - how various authors define it and in what ways they study it; second, on identifying common characteristics within different researches - whether their aims or groundings are similar. The remaining parts of the article deal with three main streams of the research of bias which have been identified on the basis of the analysis of the studied research samples. Further, selected texts representing each of the defined groups are introduced in a greater detail. DOI: 10.3126/bodhi.v2i1.2866 Bodhi Vol.2(1) 2008 p.117-135